2007
DOI: 10.1002/ab.20211
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and behavioral correlates of victim injury in serious juvenile offenders

Abstract: The study examines delinquent behavior and psychopathy and assesses their relationship to victim injury in a population of 168 incarcerated juvenile delinquent males with lengthy histories of criminal and violent behavior. A series of multiple regressions found that 17% of the variance associated with level of victim injury was accounted for by a model that included the three-factor model of the Psychopathy Checklist: Youth Version [Forth, Kosson, and Hare, 2003], criminal versatility, and age of onset of crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
0
7
2
2
Order By: Relevance
“…It is important to highlight the fact that, at least regarding self-reported delinquency and crime seriousness, significant differences were previously present when not controlling for age of crime onset, and that the presence of the covariable statistically affected those two dependent variables (i.e., they became non-significant). Our results do not corroborate previous studies in which CU traits predicted more severe antisocial behaviors and outcomes even after controlling for age of onset (McMahon et al, 2010;Stickle et al, 2009;Vitacco et al, 2007). The findings lead us to argue that additional research is needed when investigating the associations described in the literature between antisocial behaviors and psychopathic traits (e.g., Sevecke & Kosson, 2010;Van Baardewijk, Vermeiren, Stegge & Doreleijers, 2011), especially the CU dimension of psychopathic traits (e.g., Edens, Campbell, & Weir, 2007;Frick, 2009;Frick & White, 2008;Salekin & Lynam, 2010), namely taking into increased consideration the important role of early onset.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It is important to highlight the fact that, at least regarding self-reported delinquency and crime seriousness, significant differences were previously present when not controlling for age of crime onset, and that the presence of the covariable statistically affected those two dependent variables (i.e., they became non-significant). Our results do not corroborate previous studies in which CU traits predicted more severe antisocial behaviors and outcomes even after controlling for age of onset (McMahon et al, 2010;Stickle et al, 2009;Vitacco et al, 2007). The findings lead us to argue that additional research is needed when investigating the associations described in the literature between antisocial behaviors and psychopathic traits (e.g., Sevecke & Kosson, 2010;Van Baardewijk, Vermeiren, Stegge & Doreleijers, 2011), especially the CU dimension of psychopathic traits (e.g., Edens, Campbell, & Weir, 2007;Frick, 2009;Frick & White, 2008;Salekin & Lynam, 2010), namely taking into increased consideration the important role of early onset.…”
Section: Discussioncontrasting
confidence: 55%
“…Again, this was not consistent with some previous studies (e.g., Stickle et al, 2009;Vitacco et al, 2007), and raises the possibility that the relation between CU traits and frequency, diversity and severity of antisocial and criminal behaviors is moderated by age of crime onset. Therefore, also in this case, the hypothesis that was previously set was not confirmed.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Four studies summarized in Table 7 reported that CU traits were more common in youths with childhood-onset to their antisocial behavior compared to those with an adolescent-onset (Bauer, Whitman, & Kosson, 2011;Brandt, Kennedy, Patrick, & Curtin, 1997;Dandreaux & Frick, 2009;Silverthorn, Frick, & Reynolds, 2001). However, five studies reported results showing that psychopathic or CU traits predicted more severe antisocial outcomes, even when controlling for age of onset (Basque, Toupin, & Cote, 2012;Loeber et al, 2005;McMahon, Witkiewitz, Kotler, & The Conduct Problems Prevention Research Group, 2010;Stickle et al, 2009;Vitacco, Caldwell, Van Rybroek, & Gabel, 2007). Of particular note, in a large high-risk community sample (n ϭ 754), McMahon et al (2010) reported that CU traits assessed in seventh grade significantly predicted adult antisocial outcomes (e.g., adult arrests, adult antisocial personality symptoms) controlling for ADHD, ODD, CD, and childhood-onset of CD.…”
Section: Clinical and Predictive Utility Of Callous-unemotional Traitsmentioning
confidence: 99%
“…Psychopaths are highly likely to commit more sadistic (Hare, Cooke, & Hart, 1999;Holt, Meloy, & Strack, 1999;Meloy, 2000;Porter, Woodworm, Earle, Drugge, & Boer, 2003) and persistently brutal (Huss & Langhinrichsen-Rohling, 2000;Vitacco, Caldwell, Van Rybroek, & Gabel, 2007;Walsh, 1999;Williamson, Hare, & Wong, 1987) forms of violence than nonpsychopaths. Sadism, arousal from the physical and/or…”
Section: Victim Injurymentioning
confidence: 99%